Marketing channels a management view - Rosenbloom, Bert (South-Western, Cengage ‪Learning, 2013)
Marketing Channels: A Management View, 8e, International Edition is known to provide a management focus and managerial framework to the field of marketing channels. Theory, research, and practice are covered thoroughly and blended into a discussion that stresses decision making implications. This new edition reflects global, socio-cultural, environmental, and technological changes that have taken place within the industry.